Design and Implementation of University Information Service Platform Based on Data Warehouse - Wang, Xiao Guo; Jia, Ru (Applied Mechanics and Materials, 2013)
Considering the functional requirements of essential service, value-added service, prediction service and personalized service, which are demanded by users from university, enterprise and government, this paper designed an infrastructure of university information service platform using data warehouse technology. By means of the infomation resource integration method put forward by this paper, the platform realized the subject-oriented, multi-scale service to meet users service requirements and support decisions.